Q. 13

# In each case find the points where the line meets the two axes.         (i) 2x + y = 6        (ii)  x - 2y = 4        (iii) 2(x - 1) + 3y = 4        (iv) y - 3x = 9        (v)  2(x + 3) - 3(y + 1) = 0        (vi) (x - y) - y + 4 = 0

Answer :

(i) 2x + y = 6
For the point on the x-axis the value of y = 0.
Substituting for y = 0 in the equation,
2x + 0 = 6     ⇒ 2x = 6      ⇒   x = 3     ∴ The point where the line 2x + y = 6 ill touch the x-axis is (3, 0).
For the point on the y-axis the value of x = 0.
Substituting for x = 0 in the equation,
2 × 0 + y = 6                ⇒ y = 6     ∴ The point where the line 2x+y=6 will touch the y-axis is (0, 6).
(ii) x - 2y = 4
For the point on the x-axis the value of y= 0.
Substituting for y= 0 in the equation,
x - 2× 0 = 4           ⇒ x = 4      ∴ The point where the line x - 2y = 4 will touch the x-axis is (4, 0).
For the point on the y-axis the value of x = 0.
Substituting for x = 0 in the equation,
0 - 2y = 4      ⇒ - 2y = 4          ⇒ y == -2      ∴ The point where the line x = -2, y = 4 will touch the y-axis is (0, -2).
(iii) 2(x-1) + 3y = 4
For the point on the x-axis the value of y= 0.
Substituting for y= 0 in the equation,
2(x-1) + 3 × 0 = 4         ⇒ 2x -2 + 0 = 4            Þ 2x = 4 + 2 = 6                   ⇒ x = = 3       ∴ The point where the line 2(x - 1) + 3y = 4 will touch the x-axis is (3, 0).
For the point on the y-axis the value of x = 0.
Substituting for x = 0 in the equation,
2(0 - 1) + 3y = 4          Þ -2 + 3y = 4                  ⇒ 3y = 4 + 2 = 6                    ⇒ y = = 2       ∴ The point where the line 2(x-1) + 3y = 4 will touch the y-axis is (0, 2).
(iv) y - 3x = 9
For the point on the x-axis the value of y = 0.
Substituting for y = 0 in the equation,
0 -3x = 9       ∴ -3x = 9
x = -3       ∴ The point where the line y -3x = 9 will touch the x-axis is (-3, 0).

The point on the y-axis the value of x = 0.
Substituting for x = 0 in the equation,
y -3൰ = 9             ∴ y = 9       ∴ The point where the line 2x + y= 0 will touch the y-axis is (0, 9).
(v) 2(x + 3) - 3(y + 1) = 0
For the point on the x-axis the value of y = 0.
Substituting for y = 0 in the equation,
2(x + 3)-3(0 + 1) = 0              ⇒ 2x + 6 - 3 = 0                            ⇒ 2x = -3                               ⇒ x = -
∴ The point where the line 2(x + 3)-3(y + 1)=0 will touch the x-axis is (-, 0).
For the point on the y-axis the value of x = 0.
Substituting for x = 0 in the equation,
2(0 + 3)-3(y + 1) = 0           ⇒ 0 + 6- 3y- 3 = 0                         ⇒ -3y = -3                             ⇒ y = 1       ∴ The point where the line 2(x + 3) - 3(y + 1) = 0 will touch the y-axis is (0, 1).
(vi) (x - y) -y + 4= 0
For the point on the x-axis the value of y = 0.
Substituting for y = 0 in the equation,
(x - 0) - 0 + 4 = 0              ⇒ x + 4 = 0                    ⇒ x = -4       ∴ The point where the line (x - y) - y + 4 = 0 will touch the x-axis is (-4, 0).
For the point on the y-axis the value of x= 0.
Substituting for x = 0 in the equation,
(0-y)-y+4 = 0            ⇒ -y - y = -4            Þ -2y = -4                   ⇒ y = 2       ∴ The point where the line (x - y) - y + 4 = 0 will touch the y-axis is (0, 2).

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Quiz | Imp. Qs. on Coordinate Geometry39 mins
Coordinate Geometry45 mins
Basics of Coordinate Geometry43 mins
A Solid Grip on Basics of Coordinate Geometry49 mins
Quiz | Imp. Qs. of Coordinate Geometry46 mins
NCERT | Coordinate Geometry43 mins
A Solid Grip on Basics of Coordinate Geometry50 mins
Basic Understanding of Coordinate Geometry33 mins
Champ Quiz | 2-Dimension( Coordinate geometry )36 mins
Know How to Solve Complex Geometry Problems!27 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses